HIV-1 Recent Infection Testing Algorithm With Antiretroviral Drug Detection to Improve Accuracy of Incidence Estimates. (1st August 2021) - Voetsch, Andrew C.; Duong, Yen T.; Stupp, Paul; Saito, Suzue; McCracken, Stephen; Dobbs, Trudy; Winterhalter, Frieda S.; Williams, Daniel B.; Mengistu, Assegid; Mugurungi, Owen; Chikwanda, Prisca; Musuka, Godfrey; et al.
Abstract : Background: HIV-1 incidence calculation currently includes recency classification by HIV-1 incidence assay and unsuppressed viral load (VL ≥ 1000 copies/mL) in a recent infection testing algorithm (RITA). However, persons with recent classification not virally suppressed and taking antiretroviral (ARV) medication may be misclassified. Setting: We used data from 13 African household surveys to describe the impact of an ARV-adjusted RITA on HIV-1 incidence estimates. Methods: HIV-seropositive samples were tested for recency using the HIV-1 Limiting Antigen (LAg)-Avidity enzyme immunoassay, HIV-1 viral load, ARVs used in each country, and ARV drug resistance. LAg-recent result was defined as normalized optical density values ⩽1.5. We compared HIV-1 incidence estimates using 2 RITA: RITA1: LAg-recent + VL ≥ 1000 copies/mL and RITA2: RITA1 + undetectable ARV. We explored RITA2 with self-reported ARV use and with clinical history. Results: Overall, 357 adult HIV-positive participants were classified as having recent infection with RITA1. RITA2 reclassified 55 (15.4%) persons with detectable ARV as having long-term infection. Those with detectable ARV were significantly more likely to be aware of their HIV-positive status (84% vs. 10%) and had higher levels of drug resistance (74% vs. 26%) than those without detectable ARV. RITA2 incidence was lower than RITA1 incidence (range, 0%–30% decrease), resulting in decreased estimated new infections from 390, 000 to 341, 000 across the 13 countries. Incidence estimates were similar using detectable or self-reported ARV (R 2 > 0.995). Conclusions: Including ARV in RITA2 improved the accuracy of HIV-1 incidence estimates by removing participants with likely long-term HIV infection. Abstract : Supplemental Digital Content is Available in the Text.